2014
DOI: 10.1097/aog.0000000000000447
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Selective Serotonin Reuptake Inhibitors in Early Pregnancy and the Risk of Miscarriage

Abstract: Women exposed to SSRIs during early pregnancy were at increased risk of miscarriage as were women discontinuing SSRI treatment before pregnancy, and these risks were similar. Therefore, treatment with SSRIs during pregnancy should not be discontinued as a result of fear of miscarriage. LEVEL OF EVIEDENCE:: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 28 publications
1
34
1
Order By: Relevance
“…examined the relationship between antidepressant use and miscarriage using a pharmacy database. 21 The authors found an increased risk of miscarriage in those women taking antidepressants during the first trimester (1.27 HR; 95% CI 1.22-1.33) compared to women that did not. However, they found a similarly increased risk of miscarriage in those women that stopped the antidepressant prior to conceiving (1.24 HR, 95% CI 1.18-1.30).…”
Section: Discussionmentioning
confidence: 97%
“…examined the relationship between antidepressant use and miscarriage using a pharmacy database. 21 The authors found an increased risk of miscarriage in those women taking antidepressants during the first trimester (1.27 HR; 95% CI 1.22-1.33) compared to women that did not. However, they found a similarly increased risk of miscarriage in those women that stopped the antidepressant prior to conceiving (1.24 HR, 95% CI 1.18-1.30).…”
Section: Discussionmentioning
confidence: 97%
“…20 A recent study by Andersen et al examined the relationship between antidepressant use and miscarriage using a pharmacy database. 21 The authors found an increased risk of miscarriage in those women taking antidepressants during the first trimester (1.27 HR; 95% CI 1.22-1.33) compared to women that did not. However, they found a similarly increased risk of miscarriage in those women that stopped the antidepressant prior to conceiving (1.24 HR, 95% CI 1.18-1.30).…”
Section: Discussionmentioning
confidence: 99%
“…[66][67][68] Well conducted studies also suggest no increased risk for stillbirth or perinatal death with antenatal use of SSRIs. 69 70 Two large population based studies found no increased risk for hypertensive disorders in pregnancy from use of SSRIs in pregnancy among women with psychiatric disorders, although serotonin-norepinephrine reuptake inhibitors were associated with a small increased risk in one study.…”
Section: Effects Of Antidepressants In Pregnancymentioning
confidence: 99%